2021
DOI: 10.3390/ijerph18179134
|View full text |Cite
|
Sign up to set email alerts
|

Motor Function of Children with SMA1 and SMA2 Depends on the Neck and Trunk Muscle Strength, Deformation of the Spine, and the Range of Motion in the Limb Joints

Abstract: The purpose of this study was to investigate the functional relationships between selected ranges of motion of the neck, upper and lower limbs, the strength of the neck and trunk muscles, postural parameters, and the motor function of children with SMA1 and SMA2—27 children, aged 6 months-15 years, with genetically confirmed spinal muscular atrophy type 1 (19 children) and 2 (8 children) undergoing pharmacological treatment. All children were examined, according to the methodology, including the motor function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 36 publications
(40 reference statements)
5
11
0
2
Order By: Relevance
“…A manual containing all the procedures for applying the scales was used during the assessment. All items were tested without using a brace or orthoses [ 21 , 22 , 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A manual containing all the procedures for applying the scales was used during the assessment. All items were tested without using a brace or orthoses [ 21 , 22 , 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…The evaluated parameters included shoulder flexion (SF) and abduction (AbS), elbow flexion (EF), forearm pronation (PF) and supination (SF) in the upper limb, as well as hip flexion (HF), knee flexion (KF) and ankle dorsiflexion (AD—ankle dorsiflexion) in the lower limb. In addition, four parameters for detecting early musculoskeletal changes that predispose to scoliosis formation were examined [ 4 , 19 , 28 ]. The supine angle of trunk test (SATR), measuring the angle of upper (SATR-U) and lower (SATR-L) trunk rotation, and pelvic obliquity (PO), determining the value of pelvic tilt angle, were examined using a scoliometer.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the assessment with both baseline muscle MRI score and Cobb angle correlated with the nusinersen e cacy. Technical di culty of nusinersen administration in patients with severe scoliosis have been addressed [20,21], and it has been shown that deformation of spine correlates to the motor function in patients with SMA [22]. However, there were scarce information on how the severity of scoliosis affects the effect of nusinersen.…”
Section: Discussionmentioning
confidence: 99%